THE IMPLEMENTATION OF CHARACTER EDUCATION TO FOSTER LEARNERS’ CORE VALUE AT AN-NUR IBUN COMMUNITY LEARNING CENTER - Euis Rini Purwati; Agus Hasbi Noor; Nandang Rukanda (Journal Of Educational Experts (JEE), 2021)
Character education is the focus of learning that become the spirit of education in both formal and non formal institution. The aim of this research in to capture the implementation of character education in one of non formal education institutions, at An-Nur Ibun Community Learning Center Majalaya. This research conducts qualitative descriptive study, to seek empirical data and to explore deep information about character education in practice in non formal education institution. The technique used in this research is observation, interview, and literature study. Based on the result of the observation and the interview with 2 (two) tutors, there is a fact that An-Nur Ibun Community Learning Center has integrated character education into its programs. According to the research, it can be concluded that all institution programs conducted at An-Nur Ibun are able to bear and create learners who posses the five core values; religiousity, nationalist, independence, communal work, and integrity. It is expected that the five core values can highly support all learners and graduates so that they are able to survive, be enterpreneur, provide living for themselves and their families, as well as able to compete in society.